Daur Ulang Plastik Berbasis Waste to Value Menuju Ekonomi Sirkular: Analisis Bibliometrik dan Systematic Literature Review - Fatimah Andini; Devi Maulida Rahmah; Robi Andoyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Plastic waste problems require management strategies that not only reduce waste volume but also create added value through a waste to value approach. This study aims to analyze research development on waste to value based plastic recycling toward a circular economy using bibliometric analysis and systematic literature review. Data were collected from Scopus using open-access article criteria from 2021 to 2026. A total of 27 articles were analyzed bibliometrically using VOSviewer, while 25 full-text articles were synthesized through SLR. The bibliometric results show that plastic recycling, plastic waste, recycling, and valorization are dominant keywords, while activated carbon, bio-based solvents, 3D printing, and effluent treatment remain potential research areas. The SLR results indicate that plastic waste can be converted into construction materials, composites, monomers, chemicals, energy, membranes, adsorbents, catalysts, and recycled packaging. Future studies should integrate technical, environmental, economic, and regulatory evaluations..